Physical Condition Profile of Jatidiri Muda FC Academy Futsal Players in Semarang City - Pujiono, Renaldy; Amrulloh, Aziz (Java Mutiara Media, 2024)
The purpose of this study is to determine the level of physical condition of the Jatidiri Muda fc Semarang Academy futsal athletes. This study uses quantitative method research with a descriptive approach. With data collection using survey tests and physical condition measurements. The population in the study was Jatidiri Muda FC Semarang Academy futsal players. The sampling technique used total sampling with a sample of 20 athletes. The data analysis is in the form of quantitative descriptive statistics with the frequency obtained divided by the total sample multiplied by 100%. The results showed that the level of physical condition components of Jatidiri Muda Semarang futsal players was categorized as moderate or sufficient in the ability of speed with an average of 4.41 seconds, agility with an average of 16.7 seconds, flexibility with an average of 22 cm, coordination with an average of 8 times and accuracy with an average value of 28. While the ability of physical condition components that were categorized as deficient was strength with an average of 29 times in 60 seconds, cardiorespiratory endurance 28.59 ml / kg / min, explosive power with an average of 215 cm, balance with an average value of 29 seconds and reaction with an average value of 01.40 seconds. The profile of the physical condition components of Jatidiri Muda FC Semarang futsal players can be concluded to still be in the medium and less average categories. This can be one of the factors inhibiting achievement improvement in these athletes. It is necessary to evaluate and determine the right training program to improve each component of physical condition considering the data obtained from each component of physical condition which is still in the moderate and deficient category.